Effect of silver nanowires on the performance of VTP: PC71BM organic photodiodes - Md Sabri, Amirul Ashraf; Hisamuddin, Syaza Nafisah; Alwi, Siti Anis Khairani; Roslan, Nur Adilah; Nguyen, Minh Tam; Bawazeer, Tahani M.; Alsoufi, Mohammad S.; Alsenany, Nourah; Ahmad Ludin, Norasikin; Supangat, Azzuliani (Elsevier, 2022)
In the present study, the performance of a new model of organic photodiodes (OPDs) are reported by incorporating silver nanowires (AgNWs) with vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22 tetrakis(dimethylamino)-29H,31H phthalocyanine (VTP) and [6,6]-phenyl C71 butyric acid methyl ester (PC71BM) as the photoactive layer. The influence of the presence of AgNWs on the performance of OPDs was compared to that of devices without AgNWs. Our results indicate that the improvement in the OPDs with the presence of AgNWs performance such as responsivity and detectivity was markedly improved to almost three times with the integration of AgNWs on the VTP:PC71BM active layer. Our results also shows that the OPDs produced is on par with some of the conventional inorganic PDs.